The atmospheric grid of cruising on the high seas - Escher, Anton; Karner, Marie; Kerz, Christian; Rapp, Helena; Sommerlad, Elisabeth (ERDKUNDE, 2016)
The paper identifies ‘the atmospheric grid of cruising on the high seas’ as collective basis for the individual atmospheric perception. Embedded in the current academic discourse on research involving atmospheres, we developed a theoretical concept that is tailored to the particular characteristics of cruise ships. Practical experiences, empirical analysis and discursive introspections show that the atmospheric grid can be broken down into the five dimensions of ‘movement’, ‘disappearing’, ‘reflection’, ‘simulation’ and ‘guidance’. Since the analytically recognized atmospheric dimensions overlap, the ‘atmospheric grid’ is experienced as a whole on cruise ships. This forms the basis for each passenger’s individual atmospheric perception of cruising on the high seas.